1999
DOI: 10.1002/(sici)1099-0682(199911)1999:11<1995::aid-ejic1995>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Derived Structures and Molecular Properties of Nickel Dithiolenes and Related Complexes

Abstract: The molecular and electronic structure of the planar nickel dithiolene (1c, R = H) and of related complexes derived from nickel dithiolene by replacement of Ni by Pd (palladium dithiolene, 2c, R = H) or by Pt (platinum dithiolene, 3c, R = H), or by replacement of S by NH (nickel diiminolene, 1a, R = H), O (nickel dioxylene, 1b, R = H) or Se (nickel diselenolene, 1d, R = H), were studied by density functional theory using the B3LYP functional and the valence triple‐zeta basis set 6‐311+G* for all atoms except P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
63
1
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 57 publications
14
63
1
2
Order By: Relevance
“…The S atoms bonded to Ni, carry a negative charge of 0.26e and 0.19e for Ni(dddt) 2 and Ni(pddt) 2 , respectively. The previous observations for the electron population of Ni are in agreement with those reported in the literature [13,50]. The charges we calculated are typical for Ni(II).…”
Section: Charge Analysissupporting
confidence: 74%
See 1 more Smart Citation
“…The S atoms bonded to Ni, carry a negative charge of 0.26e and 0.19e for Ni(dddt) 2 and Ni(pddt) 2 , respectively. The previous observations for the electron population of Ni are in agreement with those reported in the literature [13,50]. The charges we calculated are typical for Ni(II).…”
Section: Charge Analysissupporting
confidence: 74%
“…10 for the case of the isolated Ni compound. It is observed that the intramolecular charge transfer (p-> p*) over the ligands (S,C), describes the first and strong UV-Vis transition, similar to what was found for other studied metal complexes [12,50,55]. The metal d orbital (d xz ) contributes to LUMO to a minor extent only [55].…”
Section: Spectral Characteristicsmentioning
confidence: 99%
“…On the basis of extended Hückel and DFT calculations [111,112], these absorption bands were assigned as simple HOMO-LUMO single electron transitions, however more recent works emphasize that this assignment may be somewhat misleading due to the possible multideterminantal character of the ground state wave function. As a consequence, reproduction of the absorption spectra becomes non-trivial and TD-DFT methods must be used with caution.…”
Section: Contribution Of Theoretical Calculations To the Comprehensiomentioning
confidence: 99%
“…Moreover, DFT bond lengths of second and higher row main-group elements are known to result systematically too large [39,40]. The C-S bond lengths, for instance, are overestimated by about 0.03 A.…”
Section: Resultsmentioning
confidence: 99%